IMPLEMENTASI SISTEM MINA PADI DALAM MENINGKATKAN KESEJAHTERAAN PETANI PERSPEKTIF MAQASHID SYARIAH - Nina Amaliya; Abdul Rosyid (Qawanin: Jurnal of Economic Syaria Law, 2022)
The implementation of mina padi system in the Putih Village comes from complaints of farmers who have land east of the river that are often flooded, so it makes the land less productive. So that the headman of Putih Village began the innovation of minapadi system to overcome that problem. Over time, the implementation of minapadi system can increase the welfare of farmers. The welfare obtained by these farmers is not only in the form of wealth, but also includes of soul, mind, descent, and religion. As in maqashid syariah, it is explained that welfare can be achieved if the five basic elements of life are fulfilled. The method used in this study is a qualitative method with descriptive approach. Data sources are obtained from informants, location situation, and documentation files. The results of this study are: 1) The mechanism of mina padi system was begun with land preparation used for the application of the mina padi system. Then, it is continued with the sowing of fish seeds. Putih Village used intercropping pattern with a deep rice plant model equipped with caren. 2) With the implementation of the mina padi system, the welfare obtained by farmers has increased because farmers got two types of results in one time harvest. In addition, minapadi system produced the better results, so it can increase the selling price. 3) The implementation of maqashid syariah in minapadi system namely the farmer welfare in dharuriyah discussion in maintaining religion, wealth, soul, mind, and descent.